Adapting the case method in an economics capstone research course. (November 2022) - Depro, Brooks; Rouse, Kathryn
Abstract: Recent research suggests educators can enhance the depth of capstone projects by assigning projects with real-world applications. We illustrate how the case method can be adapted for an undergraduate research experience course. We present an example case study project used in an economic consulting capstone course. Student teams receive a case narrative that includes a real-world request for a proposal. In response, they must formulate a research question, identify and analyze appropriate data to address it, and prepare several business memorandums, a final proposal, and an oral presentation to share their findings. We argue that while traditional undergraduate research helps students develop general data literacy and critical thinking skills, a case study format is better suited to simulate how these skills will be used once students enter their professional lives.